GENOTOXICTY OF MENTAWAN (POIKILOSPERMUM SUAVEOLENS) EXTRACTS USING THE ALLIUM CEPA ASSAY - Fabroa, Jedd; Mindac, Precious; Quizon, April Ann Karen; Pedro, Merbeth Christine L.; Yllano, Orlex B.; Evangelista, Ephraim Ephraim M.; Esplana, Ferdinand A.; Vegafria, Neil John V. (11th International Scholars Conference, 2016)
The use of plants as herbal medicine has been known worldwide. People believe that herbal medicine could treat their illnesses even without an established study. There was no recorded study on the genotoxicity of Mentawan (Poikilospermum suaveolens). Mentawan, a stout and woody climber is considered as an herbal medicine that effectively cure diarrhea, gastritis, and the like. This study investigated the effect of Mentawan leaf extract with the root length, root number, and chromosomal aberration of Allium cepa roots using A. cepa Assay. There were no toxicity symptoms evident on the Allium cepa roots. Analysis of variance showed no significant difference in the root number, root length, and chromosomal aberrations in different concentrations of Mentawan and the control.